2009
DOI: 10.1097/opx.0b013e3181989266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Corneal Reshaping in Hyperopic Orthokeratology

Abstract: A hyperopic OK effect was established after 1 h with increased effect with longer lens wearing time. Central fenestrations did not affect the clinical outcomes, indicating that corneal compression by the lens in the para-central region as opposed to central post lens tear film suction may be the primary mechanism behind the hyperopic OK clinical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…16 Myopic CRT is much more commonly prescribed, particularly because of its high predictability 17,18 compared with the still developing and less predictable hyperopic treatment. 19,20 We show the hyperopic lens here because of the more complex design.…”
Section: Discussionmentioning
confidence: 98%
“…16 Myopic CRT is much more commonly prescribed, particularly because of its high predictability 17,18 compared with the still developing and less predictable hyperopic treatment. 19,20 We show the hyperopic lens here because of the more complex design.…”
Section: Discussionmentioning
confidence: 98%
“…The contact lens design allows central corneal zone apical clearance to allow for central corneal steepening surrounded by the para‐central ring of bearing (Figure 3). The two current theories that have been postulated include the direct moulding from the back surface of the lens mediated by hydraulic pressures generated in the post‐lens tear film 9 or an apical suction force created within the post‐lens tear film 10 . In this case, after 3.5 years of hyperopic orthokeratology, the centrally located iron lines correlate with the area of cornea undergoing the steepening affect.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous analysis, we suggested that change to corneal curvature induced by hyperopic OK lenses was due to the corneal surface being molded towards the back surface shape of the lens (Gifford and Swarbrick, 2009). This same mechanism of effect can explain the changes in CSZ and AFZ reported here.…”
Section: Discussionmentioning
confidence: 99%